Continuity of generalized Riesz potentials for double phase functionals with variable exponents - Ohno, Takao (Array, 2021)
In this note, we discuss the continuity of generalized Riesz potentials Iρf of functions in Morrey spaces LΦ,ν(·)(G) of double phase functionals with variable exponents.